Periodo crítico de interferencia de malezas en la variedad de maní INIAP 382-caramelo en el campus de la ESPAM MFL - Ibarra Velásquez, Martha Estefanía (2018)
The objective of this research was to define the critical period of weed interference to optimize the productivity of the INIAP 382-Caramel peanut variety under the environmental conditions at the ESPAM MFL campus. The effect of periods of interference from weeds (10, 20, 30, 40, 50, days without weed control) was studied from 10 to 60 days after sowing plus one control (integrated weed management). The trial was established with a randomized complete block design (DBCA) with four repetitions, blocking the posible variability of the soil. The dominant weeds in the system were those with a narrow leaf of between 135.5-266.5 weeds/m2 in contrast with broadleaf weeds between 26.25-38.25 weeds/m2; the main competing species with the crop were the treadmill that presented 58.6%, the granadilla straw with 27.8% and the vine with 8.6% coverage. It was evidenced a high initial population of weeds, decreasing its density due to competition; however, the weight of the biomass increases due to the capture of resources (water, light, nutrients, etc.) by the weeds. Without the competition of weeds the productivity reached was 3088 kg.ha-1, the critical period from 10 to 60 days after the sowing originated a loss of the yield of 2382 kg.ha-1 that represented 77% of total production. Performing post-emergent control and integrating other weed control practices generated a higher marginal rate of return, reflecting a return of $ 44.18 for each dollar invested.